Dialogi w "Narzeczonej harambaszy" Tomasza Teodora Jeża - spontaniczność czy schematyzm = Dialogues in "Narzeczona harambaszy" by Tomasz Teodor Jeż - spontaneity or schematic approach - Żuraszek-Ryś, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The research purpose of this article is to answer the questions: how the dialogues in the novel "Narzeczona harambaszy" by T.T. Jeż were constructed, to what extent their linguistic form is an expression of respect for the currently valid linguistic conventions, and to what extent - the freedom, the creativity of the author?
Keywords: Jeż, Teodor Tomasz (pseud.; 1824-1915); powieść; dialogi powieściowe; spontaniczność; schematyzm; fictional dialogues; novel; spontaneity; schematic approach